Perinatal stem cells - Cetrulo, Kyle J.; Cetrulo, Curtis L.; Taghizadeh, Rouzbeh R. (Hoboken, N.J. : Wiley-Blackwell, 2013)
'Perinatal Stem Cells, 2nd Edition builds on the first edition to provide an updated tutorial on perinatal stem cells, including stem cells harvested from the amniotic fluid, placenta, maternal blood supply, umbilical cord and Wharton's Jelly. As in the first edition, coverage includes the underlying biology of each of the sources of pregnancy related stem cells, cell culture, and potential therapeutic uses, as well as insights on the impact of these stem cells from obstetricians and gynecologists, cardiologists, hematologists, tissue engineers, and cord blood bankers. Normally discarded as medical waste, perinatal stem cells offer a powerful therapeutic tool box alternative to the controversial embryonic stem cells. Since publication of the first edition, a burgeoning commerical industry has developed around various sources of perinatal cells, and the second edition now includes an overview of this growing industry. With contributions from some of the top academic stem cell laboratories in the United States as well as new chapters from international stem cell scientists, Perinatal Stem Cells presents an update on the cutting-edge research in the field while maintaining its signature clinical focus.'--Publisher's website.
Amniotic fluid stem cells / Sean Vincent Murphy and Anthony Atala -- Cord blood transplants : perinatal stem cells in clinical practice / Richard L. Haspel and Karen K. Ballen -- Hematopoietic stem cell development in the placenta / Katrin E.R. Ericson, Akanksha Chhabra, and Hanna K.A. Mikkolu -- Perinatal mesenchymal stem cell banking for umbilical cord blood transplantation and regenerative medicine / Rouzbeh R. Taghizadeh -- Making organ and stem cell transplantation safer : the role of mesenchymal stem cells / Hans Klingemann -- Wharton's jelly mesenchymal stem cells and immune modulation : regenerative medicine meets tissue repair / Rita Anzalone ... [et al.] -- Immunogenicity versus immunomodulation of perinatal stem cells / Bram Lutton and Raimon Duran-Struuck -- The translational potential of perinatal stem cells in clinical medicine : mesenchymal stem cells / Radbeh Torabi ... [et al.] -- Newborn stem cells : identity, function, and clinical potential / Anthony Park ... [et al.] -- Biomedical potential of human perinatal stem cells / Oleg V. Semenov and Christian Breymann -- Progenitor cell therapy for the treatment of traumatic brain injury / Alex Bryan Olsen ... [et al.] -- The human amniotic membrane : a tissue with multifaceted properties and different potential clinical applications / Maddalena Caruso, Antonietta Silini, and Ornella Parolini -- Advances and possible applications of human amnion for the management of liver disease / Fabio Marongiu ... [et al.] -- Amnion-derived cells for stroke restorative therapy / Naoki Tajiri, Loren E. Glover, and Cesar V. Borlongan -- Pregnancy-acquired fetal progenitors as natural cell therapy / Elke Seppanen, Nicholas M. Fisk, and Kiarash Khosrotehrani -- Perinatal stem cells : an industry perspective / Kyle J. Cetrulo -- Patent protection of stem cell innovations / John R. Wetherell -- Interview with Frances Verter, founder of Parent's Guide to Cord Blood Foundation / Frances Verter and Kyle J. Cetrulo -- Umbilical cord blood banking : an obstetrician's perspective / Jordan H. Perlow.
Includes bibliographical references and index.
Keywords: Stem Cells; Amniotic Fluid -- cytology; Mesenchymal Stromal Cells; Placenta -- cytology; Stem Cell Transplantation; Umbilical Cord -- cytology; Amniotic liquid; Placenta; Stem cells